Seven years of cyanide ingestions in the USA: critically ill patients are common, but antidote use is not. Issue 2 (29th May 2010) - Bebarta, Vikhyat S; Pitotti, Rebecca L; Borys, Doug J; Morgan, David L
Abstract : Background: Cyanide is a common toxin in structural fires and a salt that is ingested for suicide. However, most studies have focused on the effects of inhaled cyanide. The objective of this study was to describe the incidence of cyanide ingestions, symptoms, cardiac arrest and antidotal therapy used as reported to all US poison centres over 7 years. Methods: A retrospective review of cases over 7 years as reported to 61 poison centres in the USA was performed. Sole ingestions of cyanide were identified. A trained reviewer used a standard data collection sheet within a secured electronic database. Age, intent, clinical effects, treatments, antidotes and outcomes were recorded. One investigator audited a random sample of charts. Results: Out of 1741 exposures, 435 ingestions were identified. Most were male (68%) and the mean age was 34 years (range 1 month–83 years). 45% of cases were intentional, most commonly as a suicide attempt. 8.3% of cases died and 9% (38/435) of patients had cardiac arrest or hypotension. 13% of all cases and 26% of cases arriving at a healthcare facility received an antidote. In 35% of cases of cardiac arrest or hypotension, and in 74% of intentional ingestions, antidotes were not given. Conclusions: Suicide attempt was the most common reason for cyanide ingestion. Most of these patients died. Cardiac arrest or hypotension was common, but antidote use was not, particularly in critically ill patients. Research is needed to improve outcomes of cyanide-induced hypotension and cardiac arrest and to reduce barriers to antidote use.